2019
DOI: 10.31557/apjcp.2019.20.3.849
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Absent High-grade Cervical Intraepithelial Neoplasia (CIN) in Loop Electrosurgical Excision Procedure Specimens of Patients with Colposcopic Directed Biopsy-Confirmed High-Grade CIN

Abstract: Objective:To determine predictors of having cervical intraepithelial neoplasia (CIN) 1 or less in loop electrosurgical excision procedure (LEEP) specimens of patients with colposcopic directed biopsy-confirmed CIN 2-3. Methods: Two hundred and eighty patients with colposcopic directed biopsy-confirmed CIN 2-3 who subsequently underwent LEEP were enrolled in the retrospective study. Related clinical data were collected to determine the predictors of CIN 1 or less in LEEP specimens. Results: CIN 1 or less in LEE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Young women needed particular attention because conization could lead to cervical insufficiency. Previous studies have not found an association between age and an absence of high-grade dysplasia in conization specimens ( 13 , 14 , 20 ), which was possibly due to limited sample sizes and a lack of details regarding age groups. In this study, we found that patients aged 18–24 years were more likely to have an absence of high-grade dysplasia in conization specimens.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Young women needed particular attention because conization could lead to cervical insufficiency. Previous studies have not found an association between age and an absence of high-grade dysplasia in conization specimens ( 13 , 14 , 20 ), which was possibly due to limited sample sizes and a lack of details regarding age groups. In this study, we found that patients aged 18–24 years were more likely to have an absence of high-grade dysplasia in conization specimens.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, a significant percentage of patients (27.35%) initially diagnosed with CIN 2/3 were shown to have either no lesion or a grade of only CIN 1 after thorough examination of a conization specimen. Previous research reported that the corresponding rates ranged from 16% to 25% ( 9 , 12 14 ). The differences were related to conization indications and the definition of pathological discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations